FILSAFAT ILMU DALAM MADZHAB KRITIS JURGEN HABERMAS - Baroroh, Umdatul (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2023)
This research aims to explore Habermas' ideas about the philosophy of science in the critical schools. His idea is a counter to the positivism school which is considered to fail in understanding the humanitarian knowledge (geisteswistenschaften). The study was conducted using a library approach. Data collecting is done through a study of the literature, either in hard copy or soft copy, or online or offline. The results of this study confirm that human knowledge is not value-free. Therefore, human knowledge cannot be understood only by empirical evidence. On the other hand, human knowledge can only be understood by understanding the meaning symbolized through expression and language. Furthermore, Habermas also affirmed the importance of directing knowledge to interests that free the oppression of human life. So that human knowledge has a contribution to the struggle for justice.